Sex differences in pediatric major depressive episodes: a cross-sectional study on psychiatric symptoms in early-onset mood disorders - Massimo Apicella; Massimo Apicella; Elisa Andracchio; Giorgia Della Santa; Caterina Lanza; Clotilde Guidetti; Clotilde Guidetti; Monia Trasolini; Maria Elena Iannoni; Gino Maglio; Stefano Vicari; Stefano Vicari; et al. (Frontiers in Psychiatry)
BackgroundSex differences in psychiatric symptoms among children and adolescents with a major depressive episode (MDE) are less studied than among adults. Previous non-recent studies reported a greater severity in adolescent girls and small differences between sexes in specific symptoms. We aim to explore the differences between male and female patients in the diagnoses, comorbidities, and psychiatric symptoms in a large cohort of pediatric patients referred to a tertiary center for child and adolescent psychiatry.MethodsWe collected cross-sectional data on 382 consecutively referred patients (age 6–18 years; 73.8% female patients) with current MDEs (unipolar or bipolar) thoroughly evaluated with clinician (Children’s Depression Rating Scale-Revised; K-SADS Mania Rating Scale; Columbia Suicide Severity Rating Scale) and self and parent report (Children’s Depression Inventory-2; Multidimensional Anxiety Scale for Children-2; Child Behavior Checklist) standardized measures. Bivariate analyses were followed by a logistic regression model to assess significant predictors of the MDE phenotype of female (vs. male) patients.ResultsFemale patients were more likely to show severe MDEs (41.5% vs. 26.0%; p = 0.006), suicidal ideation (63.9% vs. 47.0%; p < 0.001) and behaviors (29.4% vs. 13.0%; p = 0.001), and non-suicidal self-injury (58.5% vs. 27.0%; p < 0.001). Male patients were more frequently diagnosed with bipolar disorder (21% vs. 11%; p = 0.012) and/or comorbid ADHD/behavior disorders (20% vs. 8.9%; p = 0.003). Male patients also had more frequently significant mixed hypo/manic symptoms (17% vs. 7.7%; p = 0.01) and were younger at the onset of the first psychiatric symptom (6.32 vs. 7.75 years; p = 0.003), onset of mood disorder (11.3 vs. 12.5 years; p = 0.005), and evaluation (14.0 vs. 15.2 years; p = 0.001). Several symptoms were significantly and independently associated with female patients diagnosed with a current MDE, including a) excessive weeping (OR 1.53; p < 0.001), b) mood lability (OR 1.50; p = 0.014), c) excessive fatigue (OR 1.38; p = 0.002), d) appetite disturbance (OR 1.28; p = 0.041), and e) attention problems (OR 1.07; p = 0.001). Distractibility (OR 0.55; p = 0.009) and conduct problems (OR 0.93; p = 0.001) were in turn correlated with MDE among male patients.DiscussionThe study confirms that female patients with MDEs exhibit more severe affective symptoms, while male patients present with more externalizing behaviors and comorbidities. We further report more mixed symptoms and bipolar disorder diagnoses in male patients, who also have an earlier onset of psychiatric symptoms. These findings are discussed also considering implications for the diagnosis of pediatric bipolar disorder. A high clinical sensitivity is needed for highlighting subtle mixed and/or atypical features in severe MDEs among girls.